2021
DOI: 10.1186/s13287-021-02458-8
|View full text |Cite|
|
Sign up to set email alerts
|

CD90low glioma-associated mesenchymal stromal/stem cells promote temozolomide resistance by activating FOXS1-mediated epithelial-mesenchymal transition in glioma cells

Abstract: Background The tumour microenvironment contributes to chemotherapy resistance in gliomas, and glioma-associated mesenchymal stromal/stem cells (gaMSCs) are important stromal cell components that play multiple roles in tumour progression. However, whether gaMSCs affect chemotherapy resistance to the first-line agent temozolomide (TMZ) remains unclear. Herein, we explored the effect and mechanism of gaMSCs on resistance to TMZ in glioma cells. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…( 11 , 42 ) Investigating a potential role of FOXS1 in chemoresistance in vivo could also be relevant and be supported by the recent study showing the role of FOXS1 on temozolomide resistance in glioma cells. ( 39 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 11 , 42 ) Investigating a potential role of FOXS1 in chemoresistance in vivo could also be relevant and be supported by the recent study showing the role of FOXS1 on temozolomide resistance in glioma cells. ( 39 )…”
Section: Discussionmentioning
confidence: 99%
“…( 26 ) In addition, it was recently reported that FOXS1 up‐regulation was related to EMT and temozolomide resistance in glioma cells. ( 39 ) Finally, FOXS1 shares a high degree of similarity with EMT‐related factor FOXC2, which promotes HCC cell invasion. Thus, our data place FOXS1 in a classical model of EMT, in which an inducible signal (TGF‐β) activates EMT‐transcription factors (FOXS1, SNAI1, and SNAI2) regulating the expression of EMT markers (VIM and CDH1) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The original article [ 1 ] contained an error in Fig. 3 B which was given wrong marking figures of NC.U87(0h) and KD.U87(0h).…”
Section: Correction To: Stem Cell Research and Therapy (2021) 12:394 Https://doiorg/101186/s13287-021-02458-8mentioning
confidence: 99%
“…However, little is known about their potential influence on chemoresistance. Recently, tumor-associated MSCs were believed to modulate the chemotherapy response by either direct cell–cell interactions with tumor cells, or by the local release of soluble factors ( 11 16 ). For instance, MSCs induce resistance to chemotherapy through the release of platinum-induced fatty acids ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an orthotopic pancreatic tumor model, targeting tumor-initiating cells by nanovesicles derived from the MSC membranes and loaded with a CXCR3 antagonist enhanced the therapy outcome when administered in combination with gemcitabine ( 15 ). Research has shown that CD90 low MSCs activate EMT and resistance to temozolomide by increasing FOXS1 expression in glioma cells ( 16 ).…”
Section: Introductionmentioning
confidence: 99%